Kepemilikan Manajerial dan Kualitas Laba Perusahan Manufaktur di Indonesia - Karolina Modeste Niwat; Teguh Erawati (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to examine the effect of company size, information asymmetry, managerial ownership and profitability on earnings quality. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period. The sampling technique used purposive sampling method. The total sample that meets the criteria is 63 companies and the analysis method uses the SPSS statistikal application. The independen variables ini this study are company size, information asymmetry, managerial ownership and profitability. The dependent variable in thus study is earnings qualit. The resukts of thus study indicate that firm size has a positive effect on earnings quality, information asymmetry has a negative effect on earnings quality, managerial ownership and profitability have a positive effect on earnings quality. Keywords : company size, information asymmetry, managerial ownership and profitability.